O PNAE, a agricultura familiar e o direito: da terra à alimentação adequada: The PNAE, Family farming, and the right: from land to adequate nutrition - Rocha, Ariza Maria; Rocha Lima, Mateus (Revista Cocar, 2022)
Este texto tem o objetivo de refletir o encontro do Programa Nacional de Alimentação Escolar (Lei nº 11.947/2009, artigo 14) com a agricultura familiar na integração do direito da terra à alimentação adequada. Trata-se de uma pesquisa bibliográfica em Bezerra (2006), Bobbio (2004), entre outros, e documentos do Portal do PNAE/FNDE e do Centro Colaborador em Alimentação e Nutrição do Escolar. Argumentamos que tal articulação vai além do combate à desnutrição e à obesidade por proporcionar o diálogo intersetorial do conhecimento local com o nacional, a inclusão do agricultor rural na Educação Alimentar e Nutricional-EAN com as questões do direito social à terra. Frisamos que existe vulnerabilidades e que são do tamanho do Brasil, contudo, também são muitas as potencialidades da articulação do PNAE, agricultura familiar e o direito social da terra. Palavras-chave: PNAE; agricultura familiar; direito. Abstract This text aims to reflect the interaction between to National School of Alimentation Program - PNAE (Law 11,947/2009 of June 16, 2009, Article 14) and family farming, resulting in the integration between the right to land and adequate nutrition. This bibliographical research is supported by the works of Bezerra (2006), Bobbio (2004), and others. We also use documents that are available at the PNAE/FNDE and the Collaborating Center for School Feeding and Nutrition – CECANE – Portals. We argue that such articulation goes beyond fighting malnutrition and obesity as it brings about an intersectoral dialog between local and national levels of knowledge, and the inclusion of rural farmers in Food and Nutrition Education-EAN with issues of the social right to land. We emphasize that there are vulnerabilities and that they are the size of Brazil, however, there are also many potentialities of the articulation of the PNAE, family agriculture, and the social right to land. Keywords: PNAE; Family Farming; Right.